Twelve weeks of exenatide treatment increases [18F]fluorodeoxyglucose uptake by brown adipose tissue without affecting oxidative resting energy expenditure in nondiabetic males - Janssen, Laura G.M.; Nahon, Kimberly J.; Bracké, Katrien F.M.; van den Broek, Dennis; Smit, Renée; Sardjoe Mishre, Aashley S.D.; Koorneef, Lisa L.; Martinez-Tellez, Borja; Burakiewicz, Jedrzej; Kan, Hermien E.; van Velden, Floris H.P.; Pereira Arias-Bouda, Lenka M.; et al. (Metabolism, clinical and experimental, 2020)
Brown adipose tissue (BAT) improves energy metabolism by combusting glucose and lipids into heat. Agonism of the glucagon-like peptide-1 receptor (GLP-1R) within the central nervous system activates BAT in mice. Moreover, in patients with type 2 diabetes, GLP-1R agonism lowers body weight and improves glucose and lipid levels, possibly involving BAT activation. Interestingly, people from South Asian descent are prone to develop cardiometabolic disease. We studied the effect of GLP-1R agonism on BAT in humans, specifically in South Asians and Europids without obesity or type 2 diabetes. Twelve Dutch South Asian and 12 age- and BMI-matched Europid nondiabetic men received 12 weeks extended-release exenatide (Bydureon) in this single-arm prospective study. Before and after treatment, BAT was visualized by a cold-induced [18F]FDG-PET/CT scan and a thermoneutral MRI scan, and resting energy expenditure (REE), substrate oxidation, body composition and fasting plasma glucose and serum lipids were determined. Appetite was rated using a visual analogue scale. Since the effect of exenatide on metabolic parameters did not evidently differ between ethnicities, data of all participants were pooled. Exenatide decreased body weight (−1.5 ± 0.4 kg, p < 0.01), without affecting REE or substrate oxidation, and transiently decreased appetite ratings during the first weeks. Exenatide also lowered triglycerides (−15%, p < 0.05) and total cholesterol (−5%, p < 0.05), and tended to lower glucose levels. Notably, exenatide increased BAT metabolic volume (+28%, p < 0.05) and mean standardized uptake value (+11%, p < 0.05) ([18F]FDG-PET/CT), without affecting supraclavicular adipose tissue fat fraction (MRI). We show for the first time that GLP-1R agonism increases [18F]FDG uptake by BAT in South Asian and Europid men without obesity or type 2 diabetes. Clinicaltrials.gov NCT03002675. •Exenatide lowers body weight and lipid and glucose levels in healthy subjects.•Exenatide increases [18F]FDG uptake by BAT measured with PET/CT scan.•Exenatide does not affect the supraclavicular BAT fat fraction measured with MRI.